Effect of processing parameter on chemical composition of of solanum tuberosum extract / Siti Nur Diyana Deraman - Deraman, Siti Nur Diyana; Ab Razak, Nureen Amni; Mohamad Nizam, Sarah Aina Qistina; Mohd Amran, Muhamad Amierul Haqimie (2021)
Solanum tuberosum extract contains a lot of bioactive compounds that have therapeutic purpose. The extraction method that involved different processing parameters are crucial to obtain the bioactive compound from Solanum tuberosum. Therefore, this current research presents the study on the effect of processing parameter on Solanum tuberosum extract. Taguchi orthogonal array design was employed to determine the effect of processing parameter towards the extraction yield of Solanum tuberosum. The processing parameters involved in this study was the drying methods, the type of solvent, the blanching methods and temperature. The highest value in response of S/N ratio indicate the most influential effect towards the extraction yield of bioactive compounds. Then, the results were statistically analysed by using one-way ANOVA. The result obtained showed that the drying method is the most influential factor as compared to the detection method and temperature. While, detection method is more influential as compared to the type of solvent. Other than that, blanching method has the most influence as compared to time and detection method. Also, temperature is more influenced as compared with the detection methods. All these processing parameters which are drying methods, detection methods, blanching methods and temperature showed significant effect with P<0.05 as compared with the other parameters. This current study showed a new insight and information on the extraction of Solanum tuberosum extract.